Attitude towards advertising among young adults: A comparative study by ethnicity - Hiram, Ting; Ernest Cyril, de Run; Teck-Weng, Jee (Universiti Malaysia Sarawak (UNIMAS), 2015)
The purpose of this study is to determine the attitude of young adults towards advertising from the perspective of ethnicity. Specifically, it seeks to find out how young adults from the Iban, Chinese and Malay communities perceive advertising so as to understand the implication of ethnicity and culture on the subject matter. A seven-factor belief model is adopted to decompose the theory of reasoned action. As such, it provides theoretical basis to explain similarities and differences of beliefs and attitude towards advertising across the three ethnic groups. Given its quantitative stance, a questionnaire-based survey was administered at universities. 316 out of 400 copies were then collected for analyses. The findings show that despite cultural differences embedded in ethnicity, beliefs and attitude of the three ethnic groups towards advertising are found largely to be similar. They can only be set apart by the effect of beliefs on the formation of attitude towards advertising. Implications and future studies are provided.